Modeling Water Absorption of Intact Bulgur During Tempering at Different Temperatures and Moisture Levels - Bay Yilmaz, Betul; Bayram, Mustafa; Turker, Nuzhet (WILEY, 2025)
This study investigated the effects of varying temperatures and initial moisture contents on the water absorption kinetics of bulgur during tempering. Three mathematical models-Peleg, modified page, and logarithmic- were fitted to the experimental data to describe moisture absorption behavior, and their predictive performance was evaluated. The best-fitting model was Peleg (R-2 = 0.968-0.995), followed by the modified page (R-2 = 0.9510-0.9914) and logarithmic (R-2 = 0.9407-0.9943) models. Hydration kinetics analysis revealed a significant change (p <= 0.05) in moisture absorption rates at the onset of tempering, coinciding with the opening of capillary channels within the wheat structure. As tempering progressed, moisture content increased until equilibrium was reached, with higher temperatures (25-45 degrees C) accelerating mass transfer. Experiments were conducted at initial moisture contents ranging from 15% to 27%, and at each level, higher temperatures were associated with higher effective moisture diffusivities (D-eff) ranging from 1.04 x 10(-9) to 1.93 x 10(-9) m(2)/s, as determined from the slope of the linearized moisture ratio (MR)-time relationship based on Fick's second law of diffusion. The activation energy (E-a) for bulgur hydration ranged from 10.41 to 21.13 kJ mol(-1), decreasing with increasing moisture contents, suggesting greater sensitivity to temperature changes at lower initial moisture levels. These results demonstrate the effectiveness of mathematical modeling as a tool for optimizing tempering conditions, enhancing hydration efficiency, and improving process control in bulgur production.
Keywords: bulgur; logarithmic model; mathematical modeling; modified page model; Peleg model; water absorption; HYDRATION KINETICS; COOKING; TIME; Food Science & Technology